2016
DOI: 10.1063/1.4945593
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic response enhancement at the polymorphic phase boundary in piezoelectric materials

Abstract: Polymorphic phase boundaries (PPBs) in piezoelectric materials have attracted significant interest in recent years, in particular because of the unique properties that can be found in their vicinity. However, to fully harness their potential as micro-nanoscale functional entities, it is essential to achieve reliable and precise control of their piezoelectric response, which is due to two contributions known as intrinsic and extrinsic. In this work we have used a (K,Na)NbO3-based lead-free piezoceramic as a mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
3
19
3
Order By: Relevance
“…Furthermore, the core-shell type microstructure could have an additional effect on the polarisation switching characteristics. In contrast, Ochoa et al [27] found that (K0.44Na0.…”
Section: Ferroelectric Propertiesmentioning
confidence: 86%
“…Furthermore, the core-shell type microstructure could have an additional effect on the polarisation switching characteristics. In contrast, Ochoa et al [27] found that (K0.44Na0.…”
Section: Ferroelectric Propertiesmentioning
confidence: 86%
“…[33] have recently reported that, in addition to the intrinsic contribution, the extrinsic contribution (domain wall contribution) also maximizes in a PPB region. Thus, the extrinsic contribution is also responsible for improving the functional properties at the PPB [33]. Despite the progress achieved recently, a fundamental question nevertheless arises:…”
Section: Introductionmentioning
confidence: 99%
“…5b, when x ≤ 0.3 the characteristic XRD peak around 45°splits obviously, showing two 002 and 200 reflections. Its peak intensity ratio (I 002 /I 200 ) is close to 2/1, which is the characteristics of orthorhombic (O) phase [32,33]. For the samples with x = 0.06, two peaks are merged into a single peak, a characteristic of rhombohedral (R) phase.…”
Section: Structure Of Cz-knlns Powdersmentioning
confidence: 88%
“…Diffraction peaks of other impurities are not observed, indicating that Li + , Sb 5+ , Ca 2+ , Zr 4+ have been completely dissolved in the KNLNS lattice during the microwave calcination stage. The characteristics of the KNLNS based ceramic crystal structures can be quantitatively identified from the relative intensities of the 002 and 200 peaks (I 002 /I 200 ) in the 2θ range of 44-47° [32,33]. As displayed in partially magnified view in Fig.…”
Section: Structure Of Cz-knlns Powdersmentioning
confidence: 99%